ANALISIS INTERDEPENDENSI PENDAPATAN PEMERINTAH DENGAN PENGELUARAN PEMERINTAH - Marlon Naibaho (Quantitative Economics Journal, 2015)
This research examines the interdependence analysis of government income to government expenditure in Indonesia, in which problems arise in this study is that government expenditure is always greater than the government income, although government income in a given year is greater than government expenditure.This research aims to look at the pattern or direction of causality between government income to government expenditure.Variables to be tested are government income and government expenditure.The data that are used are time series data 1988-2011 period.Sources of data obtained from the Central Statistics Agency of North Sumatra Province.The method used is the Granger Causality. Results of the research showed that between government income to government spending have a unidirectional causality, the causality runs from government expenditure to government income, then there is a relationship between the two variables and both have  long-term rapid adjustment towards the long-term.